2020
DOI: 10.3390/jcm9082321
|View full text |Cite
|
Sign up to set email alerts
|

Rate of Change in Bruch’s Membrane Opening-Minimum Rim Width and Peripapillary RNFL in Early Normal Tension Glaucoma

Abstract: Background: to investigate the rate of change (ROC) of Bruch’s membrane opening minimum rim width (BMO-MRW) and peripapillary retinal nerve fiber layer (RNFL) thickness in early normal tension glaucoma (NTG) patients. Methods: in this longitudinal cohort study, 115 subjects (115 eyes) diagnosed as early NTG (mean deviation > −6.0 dB) and who had completed more than five times of spectral-domain optical coherence tomography (OCT) tests with acceptable quality were included. Measurement of BMO-MRW and RNFL we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 31 publications
0
15
0
1
Order By: Relevance
“…These publications concerned other forms of glaucoma (open-angle glaucoma in adults), but their results probably also apply to juvenile glaucoma. Studies by many authors have shown that changes in BMO-MRW occur earlier than changes in RNFL in patients with open-angle glaucoma [6,8,[10][11][12][13]. In other clinical studies, it has been found that the results of the assessment of the thickness of the layer of retinal nerve fibers with BMO-MRW and RNFL are comparable in patients with glaucoma [7,15,16] and in healthy subjects [17].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…These publications concerned other forms of glaucoma (open-angle glaucoma in adults), but their results probably also apply to juvenile glaucoma. Studies by many authors have shown that changes in BMO-MRW occur earlier than changes in RNFL in patients with open-angle glaucoma [6,8,[10][11][12][13]. In other clinical studies, it has been found that the results of the assessment of the thickness of the layer of retinal nerve fibers with BMO-MRW and RNFL are comparable in patients with glaucoma [7,15,16] and in healthy subjects [17].…”
Section: Resultsmentioning
confidence: 99%
“…Measurements are made in radial scans of various meridians of the optic nerve disc. Clinical studies have shown that BMO-MRW is an objective and valuable diagnostic tool for assessing the degree of damage to the nerve fibers of the retina on the optic nerve disc [5][6][7][8][9][10][11][12][13][14][15][16][17]. Many studies have found that BMO-MRW is a more sensitive and specific parameter of the glaucomatous damage to the optic disc than the visual field, ONH and RNFL [5][6][7][8][9][10][11][12][13][14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have compared the rate of thinning between RNFLT and BMO-MRW with serial OCT examinations [6,10]. Cho and Kee [6] compared the progression rates of RNFLT and BMO-MRW in eyes with disc hemorrhage.…”
Section: Discussionmentioning
confidence: 99%
“…The earliest commercially available reference plane-independent parameter is the low-density Bruch's membrane opening-minimum rim width (BMO-MRW) parameter, which quantifies 360° of rim tissue in 3D space using the cup surface as the inner rim border and the BMO disc border as the outer rim border. Articles suggest that the BMO-MRW is the same as or better than both RNFL thickness and reference plane-dependent rim area for diagnosing glaucoma and monitoring disease progression [ 32 , 33 , 34 ▪▪ ].…”
Section: The Optic Nerve: Bruch's Membrane Opening-minimum Rim Width ...mentioning
confidence: 99%